KNOWLEDGE AND PERCEPTION OF CAUSES OF GROSS HAEMATURIA AMONG THE INHABITANTS OF KWALKWALAWA RIVERINE SETTLEMENT OF SOKOTO - Isah; Giro, Musa; Yahaya; Awosan; Ibrahim; Raji (International Journal of Research -GRANTHAALAYAH, 2017)
Blood in the urine is a common condition seen in people living around the riverine area which may result from bleeding anywhere along the urinary tract. Schistosomiasis is considered to be the commonest cause of haematuria among the inhabitants of riverine areas. Urinary schistosomiasis affects more than 200 million people worldwide and poses a threat to 600 million in more than 76 countries (WHO, 1993). In Africa alone, about 192 million cases of schistosomiasis have been reported; with Nigeria ranking the highest (15% of cases) followed by the United Republic of Tanzania (about 10% of the cases) and the Democratic Republic of Congo and Ghana with 7-8% each. A descriptive cross sectional survey was conducted among the inhabitants of Kwalkwalawa village in Wamakko local government Sokoto state, Nigeria. Majority of the respondents (81.4%) had passed bloody urine at one time of their life-time, unfortunately only 3.1% of the affected respondents had ever being to Hospital for treatment. Only 5.7% relates hematuria to contact with river water and the Knowledge score of gross hematuria revealed that only 11.4% have good knowledge of the disease. Perceived Social determinants of the disease in the environment include; Farming, Fishing, washing and Bathing in the River as well as fetching for Domestic use. The lack of proper knowledge of the cause of the disease and insufficient safe water supplies coupled with inadequate health care facilities may have influenced the infection rate and distribution of the disease in the area. In conclusion the study was able to find out a high prevalence of hematuria among the inhabitants of this study area, however, there is poor knowledge of the cause of bloody urine. Most of the respondents believed that bloody urine can be cured and prevented, but few relate it to drug treatment.